The neuroscience of sleep and dreams - McNamara, Patrick, 1956- (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2023)
"The Neuroscience of Sleep and Dreams provides comprehensive coverage of the basic neuroscience of both sleep and dreams for upper-level undergraduate and graduate students. Unlike other introductory texts, it emphasizes the social nature of sleep and dreams, and links the latest science to established evolutionary theory"--
BIBINDX
Keywords: Sleep -- Physiological aspects; Dreams -- Psychological aspects